TUGAS DAN WEWENANG BADAN WAKAF INDONESIA KALIMANTAN BARAT DALAM MENINGKATKAN KAPABILITAS NAZHIR MENURUT UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF - Akmal, Riyadh; Marluwi, Marluwi; Ardiansyah, Ardiansyah (Al-Usroh, 2024)
The purpose of this study is to determine: 1) Duties and authorities of BWI West Kalimantan in increasing the capabilities of Nazhir. 2) Conformity of the implementation of the duties and authorities of West Kalimantan BWI with Law Number 41 of 2004 concerning Waqf. This study uses a qualitative research method with a normative juridical approach. The techniques used in data collection are interviews and documentation. The data analysis technique in this study uses a descriptive-analytical analysis, which is an analysis based on the data obtained, then described, analyzed and concluded. Based on the analysis it can be concluded that: 1) The duties and authorities of the West Kalimantan BWI in improving the capabilities Nazhir are in the form of coaching. The guidance carried out by BWI West Kalimantan is in the form of socialization and training which is realized through seminars and programs in collaboration with the Ministry of Religion. 2) The duties and authorities of West Kalimantan BWI in improving the capability of nazhir are in accordance with the formulation of Law Number 41 of 2004 concerning waqf, which is regulated in Article 49 Paragraph 1 concerning the duties and authorities of BWI, then explained in Government Regulation Number 42 of 2006 Article 53.